EFEKTIVITAS KOMUNIKASI TERAPEUTIK TERHADAP PENURUNAN INTENSITAS NYERI PERSALINAN KALA I FASE AKTIF - Anthoneta J. Hitipeuw; Ismiyanti Achmad; Laorina Regel (Jurnal Kebidanan, 2022)
Pain due to uterine contractions causes discomfort that is shown by various individual responses. When facing the delivery process, not all mothers can calmly face the process, so health workers, especially midwives, must be able to provide quality care. Efforts to reduce labor have been carried out, there are various ways that do not hinder the labor process and are not harmful to the fetus. One of them with non-pharmacological therapy, namely therapeutic communication. This study aims to determine the effectiveness of therapeutic communication on the intensity of labor pain in the active phase of the first stage. This research was conducted in RSUD dr. M. Haulussy Ambon. The research design used was a quasi-experimental design with only a post-test with a control group using a questionnaire and a pain scale observation sheet. The results of the study obtained a p value of 0.003 which means that there is a difference in pain intensity in the first stage of the active phase between the intervention groups. The conclusion of the study is that therapeutic communication effectively affects the intensity of labor pain and as a midwife may be able to apply therapeutic communication as an effort to reduce pain.